(untitled) (Research, Society and Development, 2020)
HIV is known to progressively destroy certain white blood cells called CD4 + lymphocytes. Lymphocytes help to defend the body against foreign cells, infectious organisms and cancer. Thus, people are vulnerable to attack by many other infectious organisms. Many of the complications of HIV infection are usually the result of other infections and not HIV infection directly. Thus, this research aimed to describe the main relationships between covid-19 infection in patients with HIV. It is an integrative review, a careful research method used to demonstrate the knowledge produced on a given subject or theme. To carry out this study, the following databases were consulted: MEDLINE, LILACS, Scholar google and SCIELO. The Health Sciences Descriptors (DeCS) were used in an associated way: HIV, AIDS, COVID-19, complication and Virus infections. After applying the inclusion criteria, 8 studies remained. The included studies were tabulated and critical and corroborative reviews were made between each of them. COVD-19 is a serious disease and all people living with HIV should take all recommended preventive measures to minimize exposure and prevent infection with the SARS-CoV-2 virus. As in the general population, elderly people living with HIV or people living with HIV with heart or lung problems may be at a higher risk of being infected by the virus and having more severe symptoms. followingˈfälōiNG Traduções de following AdjetivoFrequência seguinte following, next, ensuing seguido following, straight, consecutive imediato immediate, instant, prompt, direct, next, following Substantivo oséquito retinue, following, train, suite, escort, cortege acomitiva entourage, retinue, company, train, suite, following osdiscípulos following ospartidários following ocortejo procession, cortege, courtship, train, following